SPATIAL AND TEMPORAL MONITORING OF THE JOVIAN ATMOSPHERE. - CUNNINGHAM, CINDY CAROLYN. (The University of Arizona., 1987)
An observational program was designed for systematic spatial and temporal monitoring of the Jovian atmosphere at several wavelengths chosen for their different absorptive properties. The weak broadband (5Å/pixel) CH₄ absorptions (6190 and 7270Å) probe the deep (2-4 bars) cloud layer while the stronger band at 8900Å probes the upper 400-600 mbars. The high resolution (~50mÅ/pixel) 3-0 H₂ quadrupole wavelengths probe to about 1-2 bars. The gradual increase in the measured equivalent widths of the H₂ quadrupole lines from the east to west limb is most likely indicative of a diurnal change in the vertical cloud structure. Such a variation is consistent with the properties of a convective layer driven by internal heat, with solar heat deposited at the top. The CH₄ data from the same time period was modelled for the south tropical zone. Since these absorptions are sensitive to several atmospheric layers it is difficult to separate the effects of the various cloud parameters on the [(I/F)(band)]/[(I/F)(cont)] values. There are no obvious limb to limb variations in these bands but several cloud parameters may be changing simultaneously, introducing compensating affects on the [(I/F)(band)]/[(I/F)(cont)] values. The two limbs may not, therefore, appear significantly different even if they are representative of substantially different cloud structures. The June 1983 H₂ data has been modelled at seven different latitudes and cloud structure differences are indicated. The average models representing the belt regions require somewhat thinner optical depths for the upper ammonia cloud (τ(cl) = 3-4.5) than the zones (τ(cl) = 5.5-6.5) or the equatorial region (τ(cl) = 6.5-7). These data also provide some constraints on the thermodynamic state of the hydrogen. A model atmosphere with only "normal" hydrogen (ortho-H₂ to para-H₂ of 3:1) is not able to fit both of the 3-0 lines simultaneously. Model atmospheres with all of the hydrogen in a state of equilibrium fit the two lines much better. Models with small amounts of disequilibrium hydrogen in the upper atmosphere also provide reasonable average fits to our H₂ data and cannot be easily distinguished from those that incorporate only equilibrium hydrogen at all levels or from those which incorporate "normal" in the top 300 mbars of the Jovian atmosphere.